Penerapan Range of Motion Cylindrical Grip pada Pasien dengan Stroke Hemoragik di Ruang Flamboyan RSUD Pasar Rebo - Pratama, Bastian Tirta; Clara, Hertuida (Maternal & Neonatal Health Journal, 2024)
Stroke is the third leading cause of death in the world and the main cause of physical disability in  productive and old age. Stroke is a term used to describe neurological changes caused by an  interruption of the blood supply to a part of the brain. Complications that will occur in stroke  sufferers is that it can cause death. The purpose of conducting a case study is to apply nursing care  to stroke patients who experience increased blood pressure through a comprehensive nursing process  approach. The research method is a descriptive method with a case study approach accompanied by  the application of evidence-based practices. Nursing care is carried out on a male patient, named  Mr. N is 51 years old with a medical diagnosis of non-hemorrhagic stroke at Pasar Rebo Hospital  Jakarta on March 14-16 2022. The results of the study obtained five nursing problems, namely  ineffective cerebral tissue perfusion, risk of decreased cardiac output, risk of nutritional deficits,  physical mobility barriers, nursing deficits self. At the implementation stage, the authors did 10-15  minutes of foot reflexology therapy with a frequency of 1x/day for 3 consecutive days to lower blood  pressure. The results of nursing care and application obtained the conclusion that foot reflexology  has not been proven as a whole in reducing blood pressure. It is hoped that the results of this study  can teach foot reflexology therapy to patients and their families to reduce blood pressure.